Analisis Manajemen Risiko Proyek dengan Metode Severity Index (SI) pada Proyek Pembangunan Gedung X Kota Surakarta - Ahmad Rizky Zaidan; Koosdaryani Soeryodarundio; Setiono Setiono (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The construction of a high-rise building is a construction project that can be said to have high risk factors so that it will have a negative effect on the project schedule, quality, and costs needed. Project risk management analysis is needed to control risks and to determine risk handling to prevent the occurrence of dominant risks in construction projects. In this study, primary data collection was carried out by distributing questionnaires, while secondary data was obtained through data from projects and literature studies. The data obtained from the questionnaire will be analyzed for risk variables using the Severity Index (SI) method. Meanwhile, the risk level analysis uses the Probability Impact Matrix (PIM). The results of the analysis show that there is a dominant risk that has the most influence on the time aspect is the risk of delay in material delivery with a high level of risk. The dominant risk that has the most influence on the cost aspect is the occurrence of equipment damage while working with a medium risk level. The dominant risk that has the most influence on the quality aspect is that the quality of the material is not in accordance with the quality specifications with a medium risk level.